Positive Discipline in Families and Couples (Journal of Parents and Teachers, 2023)
Positive  Discipline  is  a  methodology  based  on  Alfred  Adler's  Individual  Psychology,  which  promotes  relationships  of  respect and  responsibility  in  family  contexts.
Keywords: positive discipline; sense of belonging and significance; gentleness and firmness; Alfred Adler